Ultrasound Guided Versus Cystoscopy Guided Obturator Nerve Block (ONB) in Transurethral Resection of Bladder Tumours (TURBT): A Comparison of Haemodynamic Status of the Patients - Zunaid, Md; Zunaid, Taniza Jabin; Chakma, Shuchana; Deb, Gopal; Amin, Md Ruhul; Saddam, Abdullah Md; Jabed, Md; Mohammad, Taneem; Begum, Rabeya (Bangladesh Journal of Medical Science, 2023)
Background: Selective obturator nerve block (ONB) is a current trend in transurethral resection of bladder tumour (TURBT), which is easy to administer, safe and prevents some major complications during operation. Objective: To compare the haemodynamic status of two groups of patients underwent two different techniques of obturator nerve block during TURBT operation – ultrasound guided ONB vs. cystoscopy guided ONB. Methods:This prospective, observational study was conducted in the Department of Anaesthesia, Analgesia, Palliative and Intensive Care Medicine, Dhaka Medical College Hospital, Dhaka, from September 2018 to August 2019. A total of 60 selected patients were randomly allocated into two groups: ultrasound guided ONB (group A) and cystoscopy guided ONB (group B) i.e., 30 in each group. Then heart rate and blood pressure were assessed at different point during and after surgery. Results: Mean age of the patients was 54.7±8.53 years. In total, 34(57%) cases were male and 26(43%) were female. Male to female ratio was 1.3:1. In group A, 19(63.3%) patients had ASA II status and 11(36.7%) had ASA III status, while in group B, the numbers were 18(60%) and 12(40%) respectively. There was no significant difference in demographics and ASA status between two groups (P>0.05). Average onset of obturator nerve block was faster in group A (8.17±1.4 min) than group B (11.3±2.68 min), (P<0.001). Mean heart rate at baseline, at the end of the operation and postoperative room were found 77.56±2.69 and 76.35±3.09, 77.16±1.59 and 75.67±2.21, 76.34±6.24 and 75.67±6.42 in group A and B respectively, while simultaneous recorded mean systolic blood pressure were 115.23±5.56 and 116.45±5.82, 118.73±1.63 and 118.54±1.72, 116.73±3.32 and 116.37±4.13 respectively and mean diastolic pressure were 78.82±1.67 and 79.87±2.98, 77.68±2.34 and 77.18±4.15, 73.63±1.15 and 73.53±2.28 respectively. However, the differences in haemodynamic status between two groups were not statistically significant(P>0.05). Conclusion: Our data suggest no difference between two techniques in terms of changes in haemodynamic status of the patients who underwent TURBT operation. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 348-352